Produk Fermentasi Tradisional Indonesia Berbahan Dasar Pangan Hewani (Daging dan Ikan): A Review - Rizka Mulyani; Prakoso Adi; John Jackson Yang (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
Indonesia as an archipelagic country is rich in ethnicity and culture. This condition causes Indonesia to have a lot of uniqueness, one of which is traditional food. Traditional foods are varied from traditional non-fermented foods to traditional fermented foods. Based on the essential ingredients, traditional fermented foods from Indonesia can be grouped into 2 types, plant-based, and animal-based fermented foods. Information about plant-based fermented foods has been widely discussed, one of which is tempeh. However, a comprehensive discussion of traditional animal-based fermented food products, especially meat and fish, is rarely found. Therefore, the discussion on this topic can be a new thing to provide information to the public about Indonesia's treasures from a culinary perspective. This review discusses several traditional fermented foods from Indonesia, such as shrimp paste (terasi), urutan, budik, bekasam, naniura, buntilan/bontot, and ikan peda. In most cases, these foods utilize lactic acid bacteria (LAB) for their manufacture. This article is expected to be able to complete information about traditional fermented food products from Indonesia, as well as to promote the treasures of culinary origins from Indonesia to the societies.